PENGARUH PENANAMAN MODAL ASING (PMA), PENANAMAN MODAL DALAM NEGERI (PMDN), DAN PENGELUARAN PEMERINTAH DAERAH TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BONE - Nurkumiana Nurkumiana (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
This study employed quantitative descriptive approach whichexamined the correlation between FI, DI, and local government spending toward GRDP in Bone. Data used were secondary data. Data were collected through interview and documentation. Data were analyzed by employing quantitative technique with inferential statistic approachwhich tested the classical assumption and multiple linear regression analysis.The results of the study revealed that: (i) simultaneously, FI, DI and local government spending gave positive and significant influence toward GRDP in Bone. (ii) partially, FI and local government spending gave positive and significant influence toward GRDP in Bone, however,partially, DIgave negative influence and not significant toward GRDP in Bone. The increase of FI and local government spending would increase GRDP in Bone; whereas, the increase of DI would not increase GRDP in Bone. Keywords: FI, DI, local government spending, GRDP